2009
DOI: 10.1097/qad.0b013e32832e463a
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and long-term HIV outcomes in coinfected HAART recipients

Abstract: Chronic hepatitis B (CH-B) is common among HIV-infected individuals and increases liver-related mortality in the absence of highly active antiretroviral therapy (HAART). The impact of CH-B on long-term HAART outcomes has not been fully characterized.Methods-To address this question, HAART initiators enrolled in the Multicenter AIDS Cohort Study (MACS) were retrospectively analyzed. Subjects were classified by hepatitis B category based on serology at the time of HAART initiation. The association of CH-B with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 20 publications
10
79
1
1
Order By: Relevance
“…Moreover, non-Caucasian people and women had a signifi cantly lower risk of being anti-HBc positive. The association between male gender and a high anti-HBc prevalence was also observed in previous studies 16,43,44 and can be explained by males' higher rate of promiscuity and more frequent exposure to risk factors for transmission 5 . The association between anti-HBc and age over 40 years that we observed in our study can be explained by the increased chance of HBV infection that results from a longer lifespan and life time exposure to unprotected sex, unprotected sexual relationships and mother-to-child transmission.…”
Section: Informed Written Consent Was Obtained From All Participantssupporting
confidence: 78%
“…Moreover, non-Caucasian people and women had a signifi cantly lower risk of being anti-HBc positive. The association between male gender and a high anti-HBc prevalence was also observed in previous studies 16,43,44 and can be explained by males' higher rate of promiscuity and more frequent exposure to risk factors for transmission 5 . The association between anti-HBc and age over 40 years that we observed in our study can be explained by the increased chance of HBV infection that results from a longer lifespan and life time exposure to unprotected sex, unprotected sexual relationships and mother-to-child transmission.…”
Section: Informed Written Consent Was Obtained From All Participantssupporting
confidence: 78%
“…For overt chronic hepatitis B virus (HBV) infection, it is known that the virus does not substantially alter the progression of human immunodeficiency virus (HIV) disease, nor does it influence HIV suppression or CD4 cell responses following the initiation of antiretroviral treatment [3][4][5] . In contrast, it is clear that HIV infection has a negative effect on HBV disease, for both acute and chronic infections.…”
Section: Introductionmentioning
confidence: 99%
“…HBV chronic infection does not seem to have an impact on HIV immunovirological evolution or response to combined antiretroviral therapy [1,4,7,8]. Nevertheless, the SMART study showed that the decrease of CD4 count and the increase of HIV viral load were more important during antiretroviral treatment interruption periods in HIV-HBV-coinfected patients than in HIV mono-infected patients [9].…”
Section: Impact Of Hbv On the Natural History Of Hiv Infectionmentioning
confidence: 91%